2010
DOI: 10.1108/02683941011013885
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the integrative approach to conflict management

Abstract: The purpose of this paper is to examine the integrative approach to conflicts.Integration is an active search for information about facts and interests -motivated by a willingness to find mutually satisfactory agreements -and is usually necessary for creating high quality settlements in conflicts. Thus, in order to understand how to avoid win-lose outcomes, or impasses, we need knowledge about factors that relate to, and promote, integration. We here use five data-sets to explore factors relating to individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 33 publications
0
19
0
2
Order By: Relevance
“…In a study of school administrators, Bartlett (2009) found that less use of the integrating conflict management style in conflict situations was linked to increased uncivil behaviors. Rognes and Schei (2010) established that the integrating approach is positively related to decision quality, satisfaction, fairness, and trust. They also found that being of the male gender negatively related to the integrative style while high achievement motivation and a good relationship (between conflicting parties) are positively related to the integrating conflict style.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In a study of school administrators, Bartlett (2009) found that less use of the integrating conflict management style in conflict situations was linked to increased uncivil behaviors. Rognes and Schei (2010) established that the integrating approach is positively related to decision quality, satisfaction, fairness, and trust. They also found that being of the male gender negatively related to the integrative style while high achievement motivation and a good relationship (between conflicting parties) are positively related to the integrating conflict style.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Burke (1970) asserted that the dominating, accommodating, and avoiding styles are related to ineffective conflict management, while integrating and compromising styles are related to more effective management of conflict. Some scholars and researchers suggest that the integrative conflict management style leads to more effective outcomes because it is based on a "win-win" orientation with a high concern for both an individual' s and the others' goals and reflects a joint search for mutual gains (Fisher, Ury & Patton, 1991;Rognes & Schei, 2010). The use of dominating conflict management styles involving a "win-lose" orientation may create a hostile work environment and negative affect.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Although avoidance may be a good choice to stay out of trouble, conflict may remain unresolved and continue to negatively affect the situation Van Vianen, 2001, Friedman et al, 2006;Lovelace et al, 2001;Liu et al, 2009;Ohbuchi and Atsumi, 2010). Integration, effort toward a mutually benefiting solution, appears to be the preferred CMS in general, as it promises a win-win outcome, particularly in a long-term relationship (Lee, 2003;Pruitt and Carnevale, 1993;Rognes and Schei, 2010). Following the integrating style may be the obliging and avoiding styles which are then followed by the compromising and dominating styles (Cai and Fink, 2002).…”
Section: Personality Traits and Conflict Management Stylesmentioning
confidence: 99%
“…Not surprisingly, integration is superior to the other strategies in generating mutually-beneficial joint outcomes and satisfaction in most situations (e.g. De Dreu, Weingart, & Kwon, 2000;Pruitt, 1981;Rognes & Schei, 2010), although recent research indicates that teams with e.g. relationship conflicts may function better when these conflicts are avoided rather than being proactively managed (De Dreu & Van Vianen, 2001;Jehn, 1997).…”
Section: Intragroup Conflictsmentioning
confidence: 97%